Teaching & Learning Guide for: How Should We Look at Rape in Early America? - Block, Sharon (History compass, 2007)
Focus Questions 1 What are the advantages or disadvantages of various approaches to studying the history of rape? How do different approaches endorse particular perspectives (either historical or contemporary) on sexual assaults? 2 What does the study of rape reveal about life in early America? What comparisons can you make to the understanding, process, or prosecution of sexual assaults in other times and places? What do these comparisons suggest about how we write the history of rape?